The Role of Social Entrepreneurship on Kampong Development in the City of Semarang - Muhammad Indra Hadi; Iwan Rudiarto (The Indonesian Journal of Planning and Development, 2018)
Social entrepreneurship (SE) could be implemented to reveal the contribution of potential business opportunity and added value creation for its surrounding community. In the context of SME and cluster development, the SE implementation is more likely to be found in the kampong area, which has a high level of kinship system. This condition makes the application of local entrepreneurship in some cases potentially forms the characteristic of kampong through the diffusion of business innovation. This research depicts how the role of social entrepreneurs is capable of creating the characteristics of creative kampong by taking the study area in Semarang City. Through the cluster business approach, the result of this research shows the entrepreneurship transformation in becoming social entrepreneurship, in line with the development of kampong to become creative kampong by the role of social entrepreneurship. This entrepreneurship transformation occurs because of the stimulation of absorbed innovation transfer massively by the community. The implementation of local entrepreneurship has indeed influenced the characteristics of kampong and in some extents, can create the identity of creative kampong in Semarang City.